2000
DOI: 10.1093/humrep/15.8.1717
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin structure assay parameters as predictors of failed pregnancy following assisted reproductive techniques

Abstract: The predictive value of sperm chromatin integrity for pregnancy outcome following in-vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) was studied in 24 men attending a university-based assisted reproductive techniques laboratory using the flow cytometric sperm chromatin structure assay (SCSA). The SCSA is a measure of the susceptibility of sperm DNA to low pH-induced denaturation in situ. The mean percentage of spermatozoa in the neat sample demonstrating DNA denaturation was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
233
3
25

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(277 citation statements)
references
References 41 publications
16
233
3
25
Order By: Relevance
“…Although the threshold, for sperm DFI in infertile men is established [5,8,15,44] the role of sperm factor in iRPL following spontaneous conception has not been extensively evaluated [3,20], and DFI cut -off value has not yet been established. This study has tried to establish a threshold value of sperm DFI in cases with iRPL following spontaneous conception for the first time in India and is amongst the few studies in the world [28,39]. Studies have suggested that pregnancy is unlikely to occur when sperm nuclear DFI is above a certain threshold value [28,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the threshold, for sperm DFI in infertile men is established [5,8,15,44] the role of sperm factor in iRPL following spontaneous conception has not been extensively evaluated [3,20], and DFI cut -off value has not yet been established. This study has tried to establish a threshold value of sperm DFI in cases with iRPL following spontaneous conception for the first time in India and is amongst the few studies in the world [28,39]. Studies have suggested that pregnancy is unlikely to occur when sperm nuclear DFI is above a certain threshold value [28,39].…”
Section: Discussionmentioning
confidence: 99%
“…This study has tried to establish a threshold value of sperm DFI in cases with iRPL following spontaneous conception for the first time in India and is amongst the few studies in the world [28,39]. Studies have suggested that pregnancy is unlikely to occur when sperm nuclear DFI is above a certain threshold value [28,39]. Using sperm chromatin dispersion test (SCD), Bellver et al [3] observed that sperm DNA fragmentation was higher in the recurrent spontaneous abortion group compared with the sperm donor group.…”
Section: Discussionmentioning
confidence: 99%
“…The need to reevaluate old test scores is best illustrated by how a reevaluation of the use of the SCSA DNA fragmentation index (DFI) scores has dramatically changed how the test results are used to direct patients to appropriate ART [16,17]. The SCSA is the only DNA integrity test with substantial scientific literature supporting the credibility of this test for use in diagnosing male infertility, and up until 2007, patients whose sperm had a DNA fragmentation index (DFI)≄30 were told that their sperm had minimal to no chance for successful ART attempts at pregnancy [22,31,32]. However, as the number of clinics using ICSI in treating their infertile couples, this DFI cut-off began to be questioned as many groups using sperm with DFIs of 30 or higher were having excellent live birth outcome rates [23,43,60].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that the percentage of progressively motile sperm is associated with pregnancy rates 16,21,22 and great care should be taken to ensure accurate measurements.…”
Section: Assessment Of Motilitymentioning
confidence: 99%